Answer:
1) (a/3) - (b/2)
2) (m/3) + (5n/12)
3) (-5m/3) + (4x/3)
4) (4x/9) + (8y/9) - (z/3)
5) (-5a/8) + (-3b/8) + (-3c/2)
Explanation:
1) 2a-3b divided by 6
(2a-3b)/6 = (2a/6) - (3b)/6 = (a/3) - (b/2)
2) 4m+5n divided by 12
(4m+5n)/12 = (4m/12) + (5n/12) = (m/3) + (5n/12)
3) 5m-4x divided by -3
(5m-4x)/(-3) = (-5m/3) + (4x/3)
4) 4x+8y-3z divided by 9
(4x+8y-3z)/9 = (4x/9) + (8y/9) - (3z/9) = (4x/9) + (8y/9) - (z/3)
5) 5a+3b+12c divided by -8
(5a+3b+12c)/(-8) = (-5a/8) + (-3b/8) + (-12c/8) = (-5a/8) + (-3b/8) + (-3c/2)